How sustainability can get a competitive advantage: State of the art for stationary battery storage systems - Benjamin Achzet; Denise Ott; Rica Fleiner; Marvin Gornik; Andrea Thorenz; Christoph Helbig (Cleaner Chemical Engineering)
Stationary battery storage systems are becoming a critical energy infrastructure around the world. Therefore, responsible handling of battery materials is a fundamental precondition to avoid future social, environmental, and political conflicts. Global battery regulations support sustainable batteries to drive new business models on reuse, remanufacturing and recycling. With strict environmental market entry barriers, the EU will set minimum sustainability standards with the new EU-Battery Directive. The US Inflation Reduction Act provides financial incentives for a scale-up of the domestic battery industry. A hotspot analysis for the residential storage system VARTA.wall shows that a combination of reuse and recycling strategies can reduce the climate change impact by up to 45% and mineral resource use by up to 50% compared to initial battery designs. However, specific sustainability criteria and manufacturer-independent standards need to be set up by politics and industry organizations to bring the necessary technical and logistic infrastructure to the market. The challenge is to set up sustainability criteria strict enough to ensure responsible material handling but still allow cost-effective, practical solutions as well as affordable battery standards. Therefore, our analysis shows the limits of current and the need for future regulations to shift market incentives to sustainable batteries and their infrastructure.